SMPDL3b modulates insulin receptor signaling in diabetic kidney disease - A. Mitrofanova (Nature Portfolio, 2019)
Sphingomyelin phosphodiesterase acid-like 3b (SMPDL3b) is a lipid raft enzyme known to affect membrane lipid composition. Here, Mitrofanova et al. show that increased expression of SMPDL3b in diabetes impairs insulin signaling and ceramide-1-phosphate (C1P) availability in podocytes, and that C1P supplementation protects mice from diabetic kidney disease.